Role of Terlipressin and Albumin for Hepatorenal Syndrome in Liver Transplantation. Issue 10 (9th August 2020) - Sharma, Pratima; Moore, Kevin; Ganger, Daniel; Grewal, Priya; Brown, Robert S.
Abstract : Hepatorenal syndrome (HRS) is one of the most ominous complications of portal hypertension in patients with decompensated cirrhosis and ascites. It is associated with very high mortality on the wait list. Liver transplantation (LT) is the most successful therapeutic option for patients with HRS. However, not all the LT candidates with HRS are able to receive a deceased donor allograft in a timely manner because it is a scarce resource and patients may need alternative best supportive treatment with systemic splanchnic vasoconstrictors and albumin as a bridge to transplant. The combination of terlipressin and albumin is efficacious in the reversal of HRS and is used worldwide. More recently, the multicenter, randomized, placebo‐controlled double‐blind study to confirm efficacy and safety of terlipressin in subjects with hepatorenal syndrome type 1 (the CONFIRM study) trial demonstrated the efficacy of terlipressin and albumin in the reversal of HRS in a North American cohort. The aim of this article is to review the role of terlipressin and albumin in LT candidates with HRS in the United States. Abstract : https://www.wileyhealthlearning.com/Activity/7160713/disclaimerspopup.aspx